The 'Unhomely' White Women of Antillean Writing. Issue 2 (July 2014) - McCusker, Maeve
<x xml:space="preserve">Abstract</x> While the field known as 'Whiteness Studies' has been thriving in Anglophone criticism and theory for over 25 years, it is almost unknown in France. This is partly due to epistemological and political differences, but also to demographic factors — in contrast with the post-plantation culture of the US, for example, whites in Martinique and Guadeloupe are a tiny minority of small island populations. Yet 'whiteness' remains a phantasized and a fetishized state in the Antillean imaginary, and is strongly inflected by gender. This article sketches the emergence of 'white' femininity during slavery, then examines its representation in the work of a number of major Antillean writers (Condé, Placoly, Confiant, Chamoiseau). In their work, a cluster of recurring images and leitmotifs convey the idealization or, more commonly, the pathologization, of the white woman; these images resonate strongly with Bhabha's 'unhomely', and convey the disturbing imbrication of sex and race in Antillean history.